EDUKASI BIJAK DAN CERDAS MENGGUNAKAN TEKNOLOGI DAN INFORMASI DI ERA DIGITAL DI DESA KIANGROKE KECAMATAN BANJARAN KABUPATEN BANDUNG - Bah’rah, Balqis Luthfiah; Luthfiah Bah’rah, Balqis; Ainy, Dhiyana Amalia Huri; Prasetyo, Erfan Dwi Prasetyo; Assyfa, Nayla Nur Assyfa; Novianti, Salma Novianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Educational seminars on wise and smart use of technology and information in the digital era in Kiangroke Village, Banjaran District, Bandung Regency are intended as an effort to increase students' awareness and effectiveness of the use of technology and information, so that students who are addicted to using technology (gadgets) are more thorough in digging up existing information. The problem that occurs is the lack of knowledge in MTs Darul Hikam students so that education about technology and information is needed. So that the purpose of this community service is to increase knowledge of the importance of technology and information and the adverse effects of technology, especially in cybercrime cases. The method carried out in this activity is situation analysis. The result of this activity was that students consisting of 40 people at MTs Darul Hikam Kiangroke Village were very enthusiastic about the existence of an educational seminar on wise and smart use of technology and information in the digital era.